2019
DOI: 10.1039/c8se00509e
|View full text |Cite
|
Sign up to set email alerts
|

High open circuit voltages in pin-type perovskite solar cells through strontium addition

Abstract: The incorporation of even small amounts of strontium (Sr) into lead-based quadruple cation hybrid perovskite solar cells results in a systematic increase of the open circuit voltage (Voc) in pin-type perovskite solar cells. We demonstrate via transient and absolute photoluminescence (PL) experiments how the incorporation of Sr significantly reduces the non-radiative recombination losses in the neat perovskite layer and specifically at the perovskite/C60 interface. We show that Sr segregates at the perovskit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 63 publications
(62 reference statements)
6
51
0
Order By: Relevance
“…27 Thus, recent efforts were dedicated to reduce these losses through surface passivation, mostly by processing nanometer-thick interfacial layers between absorber and charge-selective contacts. [28][29][30][31][32][33][34] Recently, changes of the perovskite precursor (e.g., addition of Sr 35 or an organic molecule with passivating functional groups, 36 or a substitution 5 of PbI 2 ) led to open-circuit voltages of well over 1.20 V with comparable loss-in-potential values as obtained in best n-i-p PSCs. However, the mentioned strategies often require finely tuned processing that might be complicated to implement on a large scale.…”
Section: Introductionmentioning
confidence: 94%
“…27 Thus, recent efforts were dedicated to reduce these losses through surface passivation, mostly by processing nanometer-thick interfacial layers between absorber and charge-selective contacts. [28][29][30][31][32][33][34] Recently, changes of the perovskite precursor (e.g., addition of Sr 35 or an organic molecule with passivating functional groups, 36 or a substitution 5 of PbI 2 ) led to open-circuit voltages of well over 1.20 V with comparable loss-in-potential values as obtained in best n-i-p PSCs. However, the mentioned strategies often require finely tuned processing that might be complicated to implement on a large scale.…”
Section: Introductionmentioning
confidence: 94%
“…During the past years, many studies have evaluated recombination in perovskites layers and suggested that defects at the perovskite surface or at grain boundaries as possible reasons for nonradiative recombination in neat perovskite layers . More recently, several studies have additionally highlighted the thorny problematic of the interfaces between the perovskite and charge transport layers in the actual device, due to the fast nonradiative recombination of carriers at or across these interfaces . Therefore, a detailed understanding of the losses and the underlying physical processes is essential in order to exploit the full potential of these materials in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the V oc deficit ( V oc,def ), defined as E g / q − V oc ( q is the elementary charge), is termed to quantify the voltage loss. Tremendous efforts have been put to reduce their V oc,def , including (but not limited to) crystal growth control, [ 5–10 ] GB defect passivation, [ 11–15 ] interfacial defect passivation, [ 16–23 ] and band alignment optimization. [ 24–28 ] Up to now, V oc,def of the best‐performing PSCs can be 0.32–0.35 V, [ 9,16,29 ] which is still above the radiative loss (0.27 V) estimated by the S–Q model, as shown in Figure 1b and Table 1 .…”
Section: Introductionmentioning
confidence: 99%